(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article reveals the scientific views of scientists regarding the definition of the concept of “justice”. Attention is focused on the fact that at the legislative level the specified term does not find its substantive disclosure. The author’s definition of the concept of “justice” is proposed. The category of “justice” as an object of administrative-legal research is characterized. It is argued that justice is actually a kind of “meaning” of the existence of the judiciary. The latter represents the activities of the courts, which are aimed at considering and resolving legal disputes, protecting the rights, freedoms and legitimate interests of citizens, as well as the state and society as a whole, and bringing to justice persons who have violated the law. The principles of the rule of law, legality, fairness, equality before the law and the court, adversarial nature of the parties and observance of procedural guarantees are at the heart of justice. It has been stated that as an object of administrative law research, justice is most expedient to be considered through the prism of state administration and control, the organization of the judiciary, ensuring access to justice, as well as administrative procedures accompanying the judicial process. Administrative law regulates issues of judicial jurisdiction, the interaction of the judiciary with other branches of government, the activities of law enforcement agencies in ensuring the execution of court decisions, etc.